Intellectual property protection strategy, digital governance, and the upgrading of corporate human capital structure—A quasi-natural experiment based on the construction of national intellectual property model cities - Yang, Rui Qi; Cai, Junjie (Elsevier, 2025)
Based on data from Chinese listed companies from 2000 to 2023, this paper explores the relationship between intellectual property (IP) protection strategies, digital governance, and the upgrading of corporate human capital structures. The research findings indicate that the establishment of National IP Demonstration Cities, as a form of IP protection strategy, significantly promotes the upgrading of corporate human capital structures. Furthermore, digital governance serves as a mediating factor between IP protection strategies and the upgrading of corporate human capital structures. The mediating role of digital governance exhibits heterogeneity between profit-making and loss-making enterprises.